Intent to leave academia: perceptions and challenges of nurse faculty - Nouf Afit Aldhafeeri; Fadiyah Jadid Alanazi (BMC, 2024)
Abstract Background The shortage of nursing faculty is a significant global issue affecting the nursing profession. Faculty turnover can negatively impact the institution by decreasing the number of qualified nursing faculty and disrupting the educational process. The cost of replacing departing faculty and recruiting and training new faculty may increase. Purpose To describe perceptions of nursing faculty of intentions to leave academia and to identify challenges that contribute to nurse faculty turnover in academic setting. Method A descriptive naturalistic, qualitative approach is used to explore nurses perceptions and intentions to leave academia. Results The themes identified were unexpected journey, with two sub-themes, lack of role clarity and lack of preparation/orientation, and work environment, with four sub-themes: low Salary, workload, lack of support and favoritism. Conclusion The urgency of addressing the factors that contribute to nurse faculty intending to leave academia cannot be overstated. The results of this study have direct implications for nursing schools' administrators, where these findings can provide them with, valuable insights that they can be used to implement best practices and mitigate the problem of nursing faculty turnover.